"He [the doctor] said I should go and wait for my death:" Dualities in care and support access among female cancer survivors. (March 2023) - Nwakasi, Candidus; Esiaka, Darlingtina; Pawlowicz, Abigail; Chidebe, Runcie C.W.; Oyinlola, Oluwagbemiga; Mahmoud, Kafayat
Abstract: Introduction: While some countries have positive outlooks and technology at their disposals to detect and treat cancer in its earliest stages, other countries frequently demonstrate trends of late-stage presentation and treatment hesitancy. Nigeria is a nation that has a high cancer burden, with poorer outcomes than higher income countries (HICs). To add to the body of cancer knowledge in global health, and inform relevant policies to improve cancer survivorship, our study offers insight on cancer survivors' experiences in accessing care and support in Nigeria. Methods: The study employed a qualitative descriptive method. Semi-structured interviews were conducted with a purposive sample of 30 female breast cancer survivors in Nigeria (Mage = 42 years). Their responses were transcribed, coded, and analyzed for themes. Results: The four major themes identified were: 1) views about chemotherapy and treatments; 2) support from families and others; 3) support from health care providers; and 4) religion and coping. Each of these themes include sub-themes that offer insights on the dualities of cancer survivorship. Discussion: The high cancer death rate in Nigeria may be masking the growing number of cancer survivors, especially women diagnosed with breast cancer. It is important to design interventions that not only target cancer prevention but improving the health and quality of life of those affected by cancer in Nigeria until end of life. The findings highlight a critical need for more attention on cancer survivorship in Nigeria.